Implementation of Islamic Education Curriculum in Muhammadiyah 3 Basic School Padang Sidempuan - Yusnaldi, Eka; Siregar, Hendri; Damanik, Muhd Hayyanul; Iskandar, Wahyu; Yusuf, Muhammad (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
The curriculum in Islamic education is known as the manhaj or